Análisis de la implementación de la química verde en el desarrollo agrícola sostenible en Colombia (2019)
In the present study, an analysis is made of the food security situation in Colombia and its agricultural sector, in order to implement the concept of green chemistry to reduce part of the problems presented there. In the first place, a contextualization of the concept of green chemistry is carried out, taking into account the antecedents that precede it and defining concretely the principles that support it. Then, the situation that has been lived in Colombia on food security is defined, based on the main issues to be addressed and a broader picture of the application of this concept.